HUGE EPIDERMAL CYST - A UNIQUE PRESENTATION: Huge Epidermal Cyst - Akhtar, Khalid Ibrahim; Yasin, Bilal (Pakistan Armed Forces Medical Journal, 2014)
pidermoid/sebaceous/inclusion epidermal cyst is a common skin lesion which may sometimes mimic a cancerous lesion and appear at abnormal site. Main objective of presenting this case report is to develop the insight that benign looking cutaneous/subcutaneous swellings should never be taken as benign until proved by histo-pathological examination.